2016
DOI: 10.1016/j.gendis.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota, inflammation and colorectal cancer

Abstract: Although genes contribute to colorectal cancer, the gut microbiota are an important player. Accumulating evidence suggests that chronic infection and the ensuing inflammation contributes to tumor initiation and tumor progression. A variety of bacterial species and tumor-promoting virulence mechanisms have been investigated. Significant advances have been made in understanding the composition and functional capabilities of the gut microbiota and its roles in cancer. In the current review, we discuss the novel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
151
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(171 citation statements)
references
References 162 publications
11
151
1
3
Order By: Relevance
“…Moreover, chronic intestinal inflammation has long been recognized as a prominent CRC driver . Patients affected by inflammatory bowel diseases (IBD), such as Crohn's disease or ulcerative colitis, have been reported to have an increased risk of CRC development .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chronic intestinal inflammation has long been recognized as a prominent CRC driver . Patients affected by inflammatory bowel diseases (IBD), such as Crohn's disease or ulcerative colitis, have been reported to have an increased risk of CRC development .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intra-abdominal infections, robust use of antibiotics leading to the alteration of gut microbial composition may work in concert for the incidence and progression of colorectal carcinoma, and extraintestinal cancers (breast and hepatocellular carcinoma) [109,111,[113][114][115][116][117] predominantly through the dysregulation of inflammatory and metabolic circuits. Several current studies that assessed beta diversity through 16S rRNA sequencing have illustrated structural differences amongst the gut microbiota, where samples belonging to different disease status (cancer, adenoma, or control/normal adjacent tissue) cluster in different two-dimensional spaces indicating the presence of dysbiosis [118][119][120]. Analysis of community diversity/ richness indices has also shown a significant reduction in the microbial diversity in the feces of colorectal patients in comparison to the healthy controls [119].…”
Section: Cancermentioning
confidence: 99%
“…A recent investigation revealed that gut microbiota can efficiently prevent non-steroidal anti-inflammatory drugs (NSAIDs)-induced ulcers and erosions in the small intestine [251]. Similarly, understandings on the crosstalk amongst the gut microbes, barrier function, and the inflammatory responses have provided novel dimensions in targeting the pathology of colorectal cancer and colitis-associated cancer [118,240].…”
Section: Gut Microbes As Therapeuticsmentioning
confidence: 99%
“…Different from other kinds of cancer affecting the large bowel which are caused by point mutations in several genes that control cell proliferation, survival, differentiation and migration [60], CRC is mostly attributed to environmental factors and lifestyle such as high fat diet, alcohol, red meat, smoking, obesity, or lack of physical activity [56,85]. There are several studies showing a connection between inflammatory processes and carcinogenesis, although the contribution of immunological mechanisms and inflammation to malignancy of CRC, it is not fully elucidated [86][87][88].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Helicobacter pylori which well established in the development of stomach cancer since 1994 being classified as carcinogenic by the International Agency for Research on Cancer has also been pointed out as risk factor for CRC, as the infection leads to initial inflammatory response by stimulating IL-1β production, and consequently causing epithelium injury such as metaplasia [85]. In some studies, there was an indication of increased risk of colorectal adenomas by the presence of H. pylori due to hypergastrinemia; however, there is a controversy in other metagenomic studies that did not found correlation or even did not identify the presence of the pathogen in the analyzed samples [99].…”
Section: Main Findingsmentioning
confidence: 99%